Formulasi Dan Uji Aktivitas Anti-Aging Gel Lendir Lidah Buaya (Aloe vera Linn.) - Benni Iskandar; Anita Lukman; Okla Elfitri; Safri Safri; Meircurius Dwi Condro Surboyo (JURNAL ILMU KEFARMASIAN INDONESIA, 2021)
Aging is one of the problems that occurs in the skin. The factors cause aging are either free radicals. The use of antioxidants can prevent aging. Mucous Aloe vera known to have an antioxidant effect. The purpose of this study is to get aloe vera gel that stable and has anti-aging effects. This research was conducted by making a gel of aloe vera preparations in three formulas, each with aloe vera mucous of 5% (F1), 15% (F2) and blank (F0). Evaluation of gel preparations includes organoleptic, pH, Stability checks at room and cold temperatures, Scatter test, Adhesion, homogenity, irritation and anti-aging test on the skin of the backs of volunteers using skin analyzer with measured parameters including moisture, evenness, large pores, spot, and wrinkles. Gel was used twice a day for 30 days and was carried out every week. Statistical data were analyzed using the two-way ANOVA and continued with the Tukey test. The results showed that the stable a gel of aloe vera formula was F2 with a aloe vera concentration of 15%. Anti-aging activity test results showed that aloe vera gel preparations 15% (F2) faster recovery in increasing moisture, skin smoothness, shrinking pore size, reducing spot and wrinkles.